Grouping Seleksi Penempatan Kelas Industri Untuk Siswa Menggunakan Multi-Objective Optimization on basis of Ratio Analysis - Ratih Hafsarah Maharrani; Oman Somantri (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The quality and success of a company is determined from the planning and efforts to meet the needs of Human Resources carried out in the selection process. This means that in an effective selection process good human resources can be obtained for a longer period of time. In this study, the effectiveness of student values ​​will be analyzed with a decision support system that is used to facilitate management in the selection stage of industrial class students. From the results of the assessment, the student will be recommended to become a new employee of PT BUMA who comes from the vocational level through an industry-based curriculum education program. There are 5 criteria in the process of calculating the assessment of industrial class students, including the average student report card grades, psychological test results, HRD interviews, physical checks and pre-medical. Value processing uses a decision support system with a Multi-Objective Optimization method on the basis of Ratio Analysis (MOORA) where if the greater the student's grade results, the better the rankings produced, the more in line with the criteria expected by the company. The MOORA method was chosen because it can provide ease in the ranking process by finding the best alternative from several alternatives.